Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Find a value of c such that the conclusion of the mean value theorem is satisfied for f(x) = -2x 3 + 6x - 2












Find a value of c such that the conclusion of the mean value theorem is satisfied for


f(x) = -2x 3 + 6x - 2

Grade:12

1 Answers

anjali SHARMA
8 Points
12 years ago

f(x) is a polynomial function and is continuous and differentiable for all real numbers. Let us evalute f(x) at x = -2 and x = 2

f(-2) = -2(-2) 3 + 6(-2) - 2 = 2

f(2) = -2(2) 3 + 6(2) - 2 = - 6

Evaluate [f(b) - f(a)] / (b - a)

[f(b) - f(a)] / (b - a) = [ -6 - 2 ] / (2 - -2) = -2

Let us now find f '(x).

f '(x) = -6x 2 + 6

We now construct an equation based on f '(c) = [f(b) - f(a)] / (b - a)

-6c 2 + 6 = -2

Solve for c to obtain 2 solutions

c = 2 sqrt(2/3) and c = - 2 sqrt(2/3)

Below is shown the graph of f, a secant and the two tangent corresponding to the two solutions found. The secant and the two tangents are parallel since their slopes are equal according to the mean value theorem.

 

                                        

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free